Experimental study of seismic overloading of large arch dam. - Wang, Haibo (Earthquake engineering & structural dynamics.)
A dynamic overloading model test has been carried out on a shaking table for an arch dam of 278 m in height to investigate its behaviours under strong earthquake. The model system included the arch dam with contraction joints, part of reservoir, partial foundation rock with topographic feature near the dam. A damping boundary consisting of viscous liquid has been used to simulate the effect of dynamic energy emission to far field, which made the dynamic interaction between dam and foundation in model arch dam system be represented properly. Three sets of different seismic waves of design level have been used as the input to investigate the difference in the responses of arch dam. Artificial waves of different levels have been used to verify the behaviours of arch dam under seismic overloading. Since the opening of joints during strong earthquake reduced the response acceleration and tensile arch stress, cantilever stress on downstream face exceeded the tensile strength first for the model dam. And the arch dam responded in a non-linear way when input seismic load increased. Some cracks appeared near abutments, and the damage made the natural frequency of arch dam to drop obviously, but the static function did not seem to change for the model tested.